Konsentrasi Angkak (Monascus purpureus) dan Suhu Oven Terhadap Mutu Fisikokimia, Angka Lempeng Total, dan Organoleptik Pada Dendeng Ayam Giling - Cahyani Tri Susilo, Regitha Pandu; Hartati, Fadjar Kurnia; Handarini, Kejora (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Chicken meat is a source of animal protein that can be processed into various food products, including jerky, offering a more economical alternative without compromising taste and quality, although it has the drawback of less appealing color. This study aims to determine the optimal concentration of angkak (Monascus purpureus) as a safe natural colorant to enhance the color of minced chicken jerky and evaluate the effects of angkak concentration and oven temperature on its physicochemical properties, total plate count (TPC), and organoleptic characteristics. The study used a Completely Randomized Design (CRD) with four treatments combining angkak concentrations (1% and 3%) and oven temperatures (80Â°C and 100Â°C), each replicated three times. The analyzed parameters included color (L, a, b), moisture content, protein content, TPC, and organoleptic properties (taste, color, aroma, texture). The results of the study showed that adding angkak significantly increased red color intensity and antibacterial activity, while oven temperature affected moisture and protein contents. The best treatment was found at 3% angkak concentration and 100Â°C oven temperature, yielding dark red color, protein content of 27.13â€“30.06%, TPC of 0.022 x 10âµ CFU/g, and high organoleptic acceptance. Thus, angkak canibe usedtas asnatural colorant and preservativeKfor minced chicken jerky.